Maintenance of increased bone mass after PTH withdrawal by sequential medicarpin treatment via augmentation of cAMP‐PKA pathway. Issue 11 (12th August 2022) - Sharma, Kriti; Awasthi, Pallavi; Prakash, Ravi; Khanka, Sonu; Bajpai, Ranju; Sahasrabuddhe, Amogh A.; Goel, Atul; Singh, Divya
Abstract: Osteoporosis is a metabolic bone disorder associated with impaired bone microarchitecture leading to fragility fractures. Long‐term usage of parathyroid hormone (PTH) enhances bone resorption and leads to osteosarcoma in rats which limits its exposure to maximum 2 years in human. Notably, the anabolic effects of PTH do not endure in the absence of sustained administration. Studies in our lab identified osteogenic and antiresorptive activity in medicarpin, a phytoestrogen belonging to the pterocarpan class. Considering dual‐acting property of medicarpin and limitations of PTH therapy, we envisaged that medicarpin sequential treatment after PTH withdrawal could serve as promising therapeutic approach for osteoporosis treatment. As PTH exerts its bone anabolic effect by increasing osteoblast survival, our study aims to determine whether medicarpin amplifies this effect of PTH. Our results show that PTH withdrawal led to reduced bone mineral density and bone parameters, while sequential treatment of medicarpin after PTH withdrawal significantly enhanced these parameters. Remarkably, these effects were more pronounced than 8‐week PTH treatment. Sequential therapy also significantly increased P1NP levels and decreased CTX levels and TRAP positive cells compared to PTH 8W group where CTX levels were quite high due to bone resorptive action of PTH. Protein expression studies revealed that medicarpin along with PTH betters the antiapoptotic potential compared to PTH alone, through augmentation of cyclic adenosine monophosphate‐PKA‐CREB pathway. These results proclaim that medicarpin sequential treatment prevented the reduction in bone accrual and strength accompanying PTH withdrawal and also aided in antiapoptotic role of PTH. The study points toward the potential use of medicarpin as a replacement therapeutic option postdiscontinuation of PTH. Highlights: Medicarpin restores trabecular and cortical bone loss after discontinuation of PTH therapy. Sequential therapy of medicarpin post‐PTH withdrawal suppresses the CTX levels contrary to PTH monotherapy. Medicarpin along with PTH enhances cAMP levels and RUNX2 expression in osteoblast cells. Medicarpin enhances the antiapoptotic property of PTH in osteoblast cells via promoting the PTH activation of cAMP‐PKA pathway.